A theory of the formation of animals - Hillier, William Thomas (J. Wright and Sons; Simpkin, Marshall Ltd., 1932)
A Theory of the Formation of Animals describes the details of formation of man, the structure, development, and physiology. This book is composed of seven chapters and begins with an introduction to a theory of animal formation, namely, the theory of dual constitution. This theory hypothesize that if new types of animal arise through the fusion of two animals of dissimilar kind, then one ought to find among the members of the animal kingdom some forms which might be called Type Animals. Two of these type animals are considered, the archi-annelid Polygordius and the herring (Clupea harengus). T.